Comparison of Efficacy of Oral Methotrexate versus Oral Mini Pulse Betamethasone Therapy in Treatment of Lichen Planus - Parwarish; Ghafoor, Rabia (Indus Journal of Bioscience Research, 2025)
Background and Aim: Lichen planus is a chronic, inflammatory, autoimmune disorder affecting the skin, mucous membranes, and nails, and clinically characterized by pruritic, violaceous papules that commonly involve flexural areas. The present study aimed to compare the efficacy of oral methotrexate with that of oral mini-pulse (OMP) betamethasone therapy in the treatment of patients with lichen planus. Patients and Methods: A randomized, controlled, prospective clinical study investigated 50 cases of lichen planus at the Dermatology Unit of Jinnah Post-graduate Medical Centre Karachi from December 05, 2024 to May 04, 2025. The enrolled patients randomly assigned to two categories; Group A (oral MTX 7.5 mg weekly) & Group B (OMP betamethasone 3 mg weekly for a maximum of 12 weeks). Clinical severity reduction measured using Lichen Planus Severity Index (LPSI) at baseline, 4 weeks, and 8 weeks was the primary outcomes. Itching score (symptomatic relief), relapse rates, and adverse effects were secondary outcomes measured after 3 months follow-up. Results: The overall mean age was 38.1 ± 9.9 with no significance difference between the two groups. There were 25 (50%) male and 25 (50%) female. Majority of LP cases found in skin 29 (58%) followed by 21 (42%) of Mucocutaneous. The overall mean duration of disease (months) was 5.5 ± 2.2 months. Both groups displayed significant reduction in clinical severity after 8 weeks but slightly higher in oral methotrexate group. Additionally, post-three months follow up, Group-A exhibited lower relapse rates, higher relief in itching score, and lesser adverse effects. The Reduction in LPSI Score (%) in Group-A and B was 63.2 ± 12.5 and 58.7 ± 10.3, respectively (p=0.09). Symptomatic Relief (Itching Score Reduction) in Group A and B was 5.3 ± 1.7 and 4.8 ± 1.9, respectively (p=0.21). Adverse Effects Reported in-group A was lower 2 (8%) compared to Group B 3 (12%). Conclusion: The present study observed that both treatment showed effective results in the management of lichen planus, Oral methotrexate with the added advantages of fewer relapses and better long-term tolerability. Methotrexate may be considered a viable steroid-sparing alternative in patients requiring prolonged systemic therapy.